Current Affairs of Microbial Genome-Wide Association Studies: Approaches, Bottlenecks and Analytical Pitfalls - San, James Emmanuel; Baichoo, Shakuntala; Kanzi, Aquillah; Moosa, Yumna; Lessells, Richard; Fonseca, Vagner; Mogaka, John; Power, Robert; de Oliveira, Tulio (Frontiers in Microbiology, 2020)
Microbial genome-wide association study (mGWAS) is a new and exciting research field that is adapting human GWAS methods to understand how variations in microbial genomes affect host or pathogen phenotypes, such as drug resistance, virulence, host specificity, clinical presentation and prognosis. Several computational tools and methods have been developed or adapted from human GWAS to facilitate the discovery of novel mutations and structural variations that are associated with the phenotypes of interest. However, no comprehensive, end-to-end, user-friendly tool is currently available. The development of a broadly applicable pipeline presents a real opportunity among computational biologists. Here, (i) we review the prominent and promising tools, (ii) discuss analytical pitfalls and bottlenecks in mGWAS, (iii) provide insights into the selection of appropriate tools, (ii) highlight the gaps that still need to be filled and how users and developers can work together to overcome these bottlenecks.